ANALYSIS OF THE INCREASE IN POPULATION AND LIFE EXPECTANCY ON THE LEVEL OF COMMUNITY WELFARE IN GUNUNG SITOLI CITY IN 2018-2022 - Rista Yosefa Lumban Gao; Adyanto Purba; Ilman Ashari; Jaiton Habeahan; Irma Hutagalung; Masyura Nasution (Universitas Negeri Medan, 2024)
The present study investigates the effects of rising life expectancy and population numbers onthe state of community welfare in Gunungsitoli City between 2018 and 2022. Life expectancyrose along with the substantial population boom that Gunungsitoli City had throughout thistime. Growing populations can make it more difficult to provide essential services such asinfrastructure, healthcare, and education, but longer life expectations are a reflection ofbetter living circumstances and health care. This study examines how these two factors relateto community welfare, which is determined by social, economic, and public facilityaccessibility. The findings of the study demonstrate that while longer life expectancies aregood for welfare, rapid population expansion might make it more difficult for the governmentto provide for people's fundamental requirements, hence